Experimental and Theoretical Study for Performance Enhancement of Air Solar Collectors by Using Different Absorbers - Mohammad Saleh, Ahmed A.; Rashid, Taher Abbas (Al-Khwarizmi Engineering Journal, 2017)
An experimental and theoretical study has been done to investigate the thermal performance of different types of air solar collectors, In this work air solar collector with a dimensions of (120 cm x90 cm x12 cm) , was tested under climate condition of Baghdad city with a (43° tilt angel) by using the absorber plate (1.45 mm thickness, 115 cm height x 84 cm width), which was manufactured from iron painted with a black matt. The experimental test deals with five types of absorber:- Conventional smooth flat plate absorber , Finned absorber , Corrugated absorber plate, Iron wire mesh on absorber And matrix of porous media on absorber . The hourly and average efficiency of the collectors were investigated for three values of mass flow rates (0.016 kg/s to 0.027 kg/s) for each type of collector and then the porosity for the last collector type was tested by changing the porosity of porous media. A typical air solar collector has been studied Theoretically to build a standard software for testing any type of air solar collectors with local weather data . From the experimental study it can be seen by using some obstacle material to the air flow (fins, corrugated absorber plate, iron wire mesh porous media on the absorber) could be enhanced the efficiencies not less than 4 % for finned type and 8 % for corrugated and 25 % for mesh and 30 % for porous media comparing with flat plate (smooth) collector . Theoretically, the results showed that the collector with high convention heat transfer coefficient porous media has high hourly efficiency about (η = 56 %) and iron wire mesh on absorber ( η = 52 % ), on the other side the minimum performance occurred in the flat plate absorber (η = 28 %). Comparison of results reveals that the theoretical predictions agree reasonably well with experimental results. And the difference between the theoretical and experimental efficiency in general was between (1─ 15 %).